The Life Table according to Chiang as a Method for the Description and Assessment of the Efficacy of Oral Contraceptives - Wolfrum, Christine (Methods of Information in Medicine, 1977)
At the present time, the Pearl Index is usually calculated for the assessment of the efficacy of an oral contraceptive. The Pearl Index represents an index number for the entire treatment period. The model on which the calculation is based is an urn model with the treatment months of all subjects instead of the balls.The Pearl Index cannot be interpreted as a probability, since the treatment months are the reference units. Some of these are interdependent (treatment months of one subject), while others are independent of each other (treatment months of various subjects). For an interpretation as probability, the subjects themselves must be the reference units.In order to render the presentation of only one index number for the entire treatment period meaningful, it must be assumed that the probability of pregnancy is the same for all treatment months. In reality this is not the case.The »number of pregnancies per treatment month< can be regarded as a non-stationary stochastic process; the assumption of an urn model is, therefore, inappropriate.The Pearl Index is unsuitable for the description of a stochastic process; instead, a life table analysis according to Chiang is recommended. In the life table, various probabilities are estimated per treatment month. The net probabilities can be chosen as the index number per treatment month. The prerecjuisites for the derivation of those probabilities are described.
Keywords: Pearl Index; Life Table; Oral Contraceptives